Upregulation and the clinical significance of KCNQ1OT1 and HAGLROS lncRNAs in papillary thyroid cancer: An observational study - Mutlu Icduygu, Fadime; Akgun, Egemen; Ozgoz, Asuman; Hekimler Ozturk, Kuyas; Sengul, Demet; Alp, Ebru (Ovid Technologies (Wolters Kluwer Health), 2023)
Long noncoding RNAs (lncRNAs) play an important role in regulating gene expression. Changes in their expression have been associated with many types of cancer, including thyroid cancer. This study aimed to investigate how changes in the expression of potassium voltage-gated channel subfamily Q member 1 opposite strand/antisense transcript 1 (KCNQ1OT1) and HAGLR opposite strand lncRNA (HAGLROS) lncRNAs correlate with the development and clinicopathological characteristics of papillary thyroid cancer (PTC). Reverse transcription-quantitative polymerase chain reaction was used to investigate the expression of lncRNAs in both tumor and adjacent normal thyroid tissue samples of the patients. Expressions of KCNQ1OT1 and HAGLROS were upregulated in the patients tumor samples compared to the adjacent normal thyroid samples. KCNQ1OT1 expression was linked to microcarcinoma and gender, while HAGLROS expression was linked to microcarcinoma and tumor size. When only microcarcinoma samples were evaluated, KCNQ1OT1 expression was higher in tumor tissues compared to normal tissues; however, no significant difference was observed in HAGLROS expression. Our data suggests that high expressions of KCNQ1OT1 and HAGLROS might contribute to the development of PTC and disease progression, and both lncRNAs may be potential therapeutic targets in PTC patients.
Keywords: Gene Expression Regulation, Neoplastic; Clinical Relevance; MicroRNAs; Thyroid Cancer, Papillary; Humans; RNA, Long Noncoding; Thyroid Neoplasms; Up-Regulation; Cell Proliferation; 3. Good health